Use of adjuvants for immunotherapy. Issue 8 (3rd August 2017) - Circelli, Luisa; Tornesello, Marialina; Buonaguro, Franco M.; Buonaguro, Luigi
ABSTRACT: Cancer vaccines are designed to stimulate the body's immune system to kill tumor cells. To improve their immunogenicity, vaccine antigens must be combined with adjuvants which are able to stimulate the innate immunity and potentiate the adaptive immune response. In the last years a new generation of adjuvants mimicking the natural microbial ligands have been developed. In particular, several TLR ligands have been extensively explored as vaccine adjuvants and many preclinical and clinical studies have been conducted. However, the road to approval of such adjuvants for clinical use is still to go.